THE EFFECTIVENESS OF CONTEXTUAL LEARNING USING COOPERATIVE TYPE NUMBERED HEADS TOGETHER (NHT) SETTING AND SAINTIFIC TO THE MATHEMATICAL PROBLEM SOLVING ABILITIES OF SENIOR HIGHT SCHOOL STUDENTS - Putri Solekhah; Ali Mahmudi (Jurnal Pedagogi Matematika, 2016)
This research aim to describe effectiveness of contextual learning using cooperative type Numbered Heads Together (NHT) setting and saintific to the mathematical problem solving abilities of senior hight school students. The research was quasi experimental research used control group Pterest-Posttest Design. The population in this reseacrh was for 1st grade students in Senior Hight School 1 Sedayu, Bantul. The sample of the research consist of two classes which was randomly selected that are X MIA 1 and X MIA 3 classes. First class as 1st experiment class was given by contextual learning using cooperative type Numbered Heads Together (NHT) setting, while second class as 2nd experiment class was given by saintific learning. The instrument used in this research were test instrument to measure mathematical problem solving abilities that consist of pretest and posttest also learning accomplished’s sheet to measure precentage learning accomplished according to learning plan which has been made.. The result indicated to: (1) mathematics learning by contextual learning using cooperative type Numbered Heads Together (NHT) setting is effevtive observed by student’s mathematical problem solving abilities (2) mathematics learning by saintific aproach is effevtive observed by student’s mathematical problem solving abilities (3) mathematics learning by contextual learning using cooperative type Numbered Heads Together (NHT) setting is more effective than saintific learning observed by student’s mathematical problem solving abilities.  Keywords: effectiveness, contextual, NHT, saintific, problem solving